Key Influencers of Virtual Community Knowledge-Sharing Among Chengdu University Students - Yulin, Xiao (Scholar: Human Sciences, 2025)
Purpose: This research paper aims to investigate the key influencers that significantly impact the willingness of college students to share knowledge using virtual communities in four universities in Chengdu, Sichuan. The conceptual framework proposed a causal relationship among rewards, reputation, trust, reciprocity, self-efficacy, subjective norms, attitude toward knowledge sharing, intention to share knowledge. Research design, data, and methodology: Researchers conducted a quantitative study with 500 college students from four universities in Sichuan. These students studied for over a year and actively participated in virtual communities. The sampling method involved judgmental sampling for selecting universities, quota sampling for questionnaire distribution, and convenience sampling for data collection and survey distribution. The data was analyzed using structural equation modeling and confirmatory factor analysis, evaluating model fit, reliability, and validity. Results: The attitude towards knowledge sharing is the primary and strongest predictor of the intention to share knowledge. Attitudes towards knowledge sharing are significantly driven by rewards, reputation, trust, reciprocity, self-efficacy, and subjective norms. Conclusions: Seven hypotheses met the study objectives. To promote the knowledge-sharing behavior of college students in virtual communities, university and community managers should cultivate positive sharing attitudes through various strategies.